The anti-obesity effects of rhein on improving insulin resistance (IR) and blood lipid levels are involved in endoplasmic reticulum stress (ERs), inflammation, and oxidative stress in vivo and vitro: The protective mechanism of rhein in preventing obesity. Issue 1 (1st January 2021) - Ji, Li; Gu, Huan
ABSTRACT: Rhein extensive biological effects including anti-inflammatory, antioxidant stress, and improving glucose and lipid metabolism. In the present study, the effects of rhein were examined on endoplasmic reticulum stress (ERs) and inflammation in obesity-induced rats. SD rats were fed with a normal diet or a high-fat diet. Meanwhile, rats fed with high-fat diet were also administrated with different doses of rhein for 6 weeks. The pathologic changes of pathoaorta pectoralis were evaluated using hematoxyline eosin (HE) strain, and cell apoptosis levels were investigated using TUNEL staining and flow cytometry. We also performed p62 immunofluorescent staining in 3T3-L1 cells. In the present study, we found that rhein administration exerted inhibitory effects on weight, inflammatory factor levels, and oxidative stress. Meanwhile, insulin resistance (IR), blood lipid levels and pathological injury of aorta pectoralis were also improved by rhein administration. Besides, rhein also affected ERs in peripheral blood and adipose tissue in vivo . Moreover, rhein significantly reduced cell apoptosis in aorta pectoralis and adipose tissue in vivo. According to oil red staining, adipogenic differentiation was decreased by rhein treatment in vitro. Immunofluorescence staining of p62 showed that rhein contributed to a significant increase in p62 expression in vitro. In addition, rhein treatment significantly decreased peroxisome proliferators-activated receptor (PPAR)γ levels and upregulated insulin receptor (INSR) in vitro. In summary, the anti-obesity effects of rhein were considered to be related with the involvement of ERs, inflammation, oxidative stress, PPARγ, and INSR.